A Case of Insulin Autoimmune Syndrome - MD, Amy Vora; MD, Tiwalade Awosanya; MD, Marconi Abreu (Archives of Clinical and Medical Case Reports, 2019)
Insulin autoimmune syndrome (IAS) is a rare etiology of hypoglycemia. We present the case of a woman who was diagnosed with IAS and responded successfully to glucocorticoids. A 55 year old Hispanic woman presented with symptomatic hypoglycemia. Biochemical evaluation was notable for elevated C-peptide, insulin and pro-insulin levels. Imaging to investigate for insulinoma was negative. Insulin autoantibody titers were elevated. These findings were consistent with a diagnosis of insulin autoimmune syndrome. Glucocorticoids were started in addition to dietary modification with successful reduction in hypoglycemia episodes and insulin autoantibody titers. IAS is an immune condition characterized by insulin autoantibody-insulin complexes that spontaneously dissociate leading to hypoglycemia. The diagnosis is made by confirming elevated insulin levels with concomitant low serum glucose along with elevated insulin autoantibody levels. Treatment options include dietary modification, acarbose, glucocorticoids, plasmapheresis and rituximab. Frequent medical follow up is necessary to ensure disease remission.